Internet of Robotic Things Intelligent Connectivity and Platforms - Vermesan, Ovidiu; Bahr, Roy; Ottella, Marco; Serrano, Martin; Karlsen, Tore; Wahlstrøm, Terje; Sand, Hans Erik; Ashwathnarayan, Meghashyam; Gamba, Micaela Troglia (Frontiers in Robotics and AI, 2020)
The Internet of Things (IoT) and Industrial IoT (IIoT) have developed rapidly in the past few years, as both the Internet and ‘things’ have evolved significantly. ‘Things’ now range from simple Radio Frequency Identification) (RFID) tags to smart wireless sensors; intelligent wireless sensors and actuators; robotic things; and autonomous vehicles operating in consumer, business and industrial environments. The emergence of ‘intelligent things’ (static or mobile) in collaborative autonomous fleets requires new architectures, connectivity paradigms and trustworthiness frameworks for integration of applications across different business and industrial domains. These new applications will accelerate the development of autonomous system design paradigms and the proliferation of the Internet of Robotic Things (IoRT), in which collaborative robotic things can communicate with other things; learn autonomously; interact safely with the environment, humans and other things; and gain qualities like self-maintenance, self-awareness, self-healing and fail-operational behaviour. IoRT applications can make use of the individual, collaborative and collective intelligence of robotic things as well as information from the infrastructure and operating context to plan and execute tasks in the presence of environmental uncertainties. This makes perception, location, communication, cognition, computation, connectivity, propulsion and integration of federated IoRT and digital platforms important components of new-generation IoRT applications. This paper reviews the taxonomy of the IoRT, emphasising the IoRT intelligent connectivity, architectures, interoperability and trustworthiness framework and surveying the technologies that enable application of the IoRT across different domains to perform tasks more effectively and efficiently. The objective is to provide a new perspective on the IoRT that involves communication among robots and with humans and highlight the convergence of several technologies and interactions between different taxonomies used in the literature.